2021
DOI: 10.1192/bjp.2021.169
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging-based brain-age prediction of first-episode schizophrenia and the alteration of brain age after early medication

Abstract: Background Neuroimaging- and machine-learning-based brain-age prediction of schizophrenia is well established. However, the diagnostic significance and the effect of early medication on first-episode schizophrenia remains unclear. Aims To explore whether predicted brain age can be used as a biomarker for schizophrenia diagnosis, and the relationship between clinical characteristics and brain-predicted age difference (PAD), and the effects of early medication on predicted brain age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, in the present study, we did not focus on specific brain regions to explore the alterations in brain structures caused by antipsychotic medication use in individuals with schizophrenia. A recent study 52 showed that early antipsychotic medication use might reduce the brain age gap in patients with first-episode schizophrenia. In contrast, the illness duration of the participants was longer in our study (mean: 15.56 years, ranging from 0 to 38 years), and our result showed a lack of association between medication and the brain age gap, which is consistent with the previous studies 17,18,23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, we did not focus on specific brain regions to explore the alterations in brain structures caused by antipsychotic medication use in individuals with schizophrenia. A recent study 52 showed that early antipsychotic medication use might reduce the brain age gap in patients with first-episode schizophrenia. In contrast, the illness duration of the participants was longer in our study (mean: 15.56 years, ranging from 0 to 38 years), and our result showed a lack of association between medication and the brain age gap, which is consistent with the previous studies 17,18,23 .…”
Section: Discussionmentioning
confidence: 99%
“…The comparison between remission and nonremission groups after medication indicated a significant difference in white matter tract integrity at baseline 18 . Antipsychotics can regulate the plasticity of white matter structure 19 . White matter deficits involved in SZ neurodevelopment are associated with a higher risk of treatment resistance, 20 which demonstrates the prediction of the therapeutic effect of antipsychotic drugs from the perspective of white matter function.…”
Section: Introductionmentioning
confidence: 96%
“…18 Antipsychotics can regulate the plasticity of white matter structure. 19 White matter deficits involved in SZ neurodevelopment are associated with a higher risk of treatment resistance, 20 which demonstrates the prediction of the therapeutic effect of antipsychotic drugs from the perspective of white matter function. Furthermore, recent studies reported that white matter might be a viable pharmacological target of SZ, and white matter target therapies for SZ are currently being developed.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have suggested that brain age is correlated with hypertension [8] and severity of depression [9,10], and that it is also predictive of the success of certain interventions for chronic pain [11]. Furthermore, an inflated brain age associated with schizophrenia has been shown to be partly reversed at the onset of medication [12,13]. There are a few recent review articles that give a more thorough explanation of the subject [14][15][16].…”
Section: Introductionmentioning
confidence: 99%